2014
DOI: 10.1177/1010539514548757
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in Diabetes Risk Across Native Hawaiians and Different Asian Groups

Abstract: We evaluated the impact of body mass index (BMI) and lifestyle risk factors on ethnic disparity in diabetes incidence among 89,198 Asian, Native Hawaiian, and white participants of the Multiethnic Cohort who completed multiple questionnaires. After 12 years of follow-up, 11,218 new cases were identified through self-report and health plan linkages. BMI was lowest in Chinese/Koreans, Japanese, and Filipinos (22.4, 23.5, 23.9 kg/m2). Using Cox regression, the unadjusted hazard ratios were 1.9 (Chinese/Korean), 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…Furthermore, early beta cell dysfunction has been noted in Asian patients, resulting in development of DM at a younger age. Even among Asian patients, in fact, differences in ethnic‐specific diabetes phenotypes also exist between East Asians and South Asians (Maskarinec et al., , ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, early beta cell dysfunction has been noted in Asian patients, resulting in development of DM at a younger age. Even among Asian patients, in fact, differences in ethnic‐specific diabetes phenotypes also exist between East Asians and South Asians (Maskarinec et al., , ).…”
Section: Discussionmentioning
confidence: 99%
“…This difference in incidence can perhaps be explained by race‐specific variations in the susceptibility and severity of diabetes, which was a strong independent risk factor among Native Hawaiians in our analysis. Literature has shown that there is a disproportionate burden of diabetes among Native Hawaiians, as both the prevalence and risk of diabetes is much higher for Native Hawaiians compared to European Americans . There is also evidence suggesting that diabetes may be more critical and advanced in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Literature has shown that there is a disproportionate burden of diabetes among Native Hawaiians, as both the prevalence and risk of diabetes is much higher for Native Hawaiians compared to European Americans. [26][27][28] There is also evidence suggesting that diabetes may be more critical and advanced in this population. Native Hawaiians are more frequently hospitalized for diabetes 29 and have a greater likelihood of experiencing diabetes-related complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…African Americans ( 17 ), Latinos ( 17 ), and Japanese Americans ( 18 ) are at a high risk of developing diabetes and are more likely to have a higher prevalence of severe diabetes complications compared with non-Hispanic whites ( 15 ). The reason for severe diabetes among minorities may be due to an underuse of primary care physicians, poor medication adherence, and poor understanding of their disease ( 19–21 ).…”
mentioning
confidence: 99%